1981
DOI: 10.2307/2095081
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Americans: Changing Patterns of Assimilation Over Three Generations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…On the other hand, mentoring and scholarship programs, as well as professional development workshops sponsored by these organizations and designed to improve minority group representation in specific professional areas, may imply that these new forms of ethnic organization have become more efficient and targeted than earlier forms in promoting the integration of outside groups into mainstream institutions. Other research, for example, has found ethnic professional organizations provide this integrating function for the Japanese-American community (see Montero, 1981;Fugita and O'Brien, 1985). With respect to Mexican Americans and other Latino groups, this remains an as of yet unexplored area of sociological research.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mentoring and scholarship programs, as well as professional development workshops sponsored by these organizations and designed to improve minority group representation in specific professional areas, may imply that these new forms of ethnic organization have become more efficient and targeted than earlier forms in promoting the integration of outside groups into mainstream institutions. Other research, for example, has found ethnic professional organizations provide this integrating function for the Japanese-American community (see Montero, 1981;Fugita and O'Brien, 1985). With respect to Mexican Americans and other Latino groups, this remains an as of yet unexplored area of sociological research.…”
Section: Discussionmentioning
confidence: 99%
“…Some early papers address the "three-generations hypothesis" (Lazerwitz and Rowitz 1964), but third generation members are only rarely included in contemporary analyses (see e.g. Montero 1981;Alba et al 2002). This is largely due to data constraints since a multiple-generational approach is implicit in assimilation theory (Alba et al 2002).…”
Section: The Multi-generational Family Perspectivesmentioning
confidence: 99%
“…Further to this, previous research also reveals context specific effects of ethnic identity suggesting different (either strong or weak) connections to consumer outcomes (Stayman & Deshpande, 1989). Within the sociology literature, various components of ethnic or cultural identity have been suggested (e.g., Gordon, 1964;Montero, 1981) in an effort to understand the basis of ethnicity and culture in behaviour. Cultural identity could develop through: 1 self-identity manifestations based on a particular culture or ethnic group;…”
Section: Ethnic and Cultural Constructsmentioning
confidence: 87%
“…Evidence can be found in social identity theory (e.g., Brown, Tajfel & Turner, 1980;Tajfel & Turner, 1986); acculturation psychology (e.g., Berry, 2001); sociology (e.g., Nagel, 1994); and consumer research (e.g., Schouten & McAlexander, 1995;Zaltman, 2000); and…”
Section: Cultural Identitymentioning
confidence: 99%